2021
DOI: 10.3389/fimmu.2021.659996
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Negative Breast Cancer Cells Recruit Neutrophils by Secreting TGF-β and CXCR2 Ligands

Abstract: Tumor associated neutrophils (TANs) are frequently detected in triple-negative breast cancer (TNBC). Recent studies also reveal the importance of neutrophils in promoting tumor progression and metastasis during breast cancer. However, the mechanisms regulating neutrophil trafficking to breast tumors are less clear. We sought to determine whether neutrophil trafficking to breast tumors is determined directly by the malignant potential of cancer cells. We found that tumor conditioned media (TCM) harvested from h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 96 publications
7
68
1
Order By: Relevance
“…The evidence that increased levels of neutrophils (both peripheral and in primary tumors) in triple-negative and HER2-positive tumors are associated with tumor progression and dismal prognosis is indicative of a prevalent N2 phenotype in these tumors. Consistently, overexpression of N2-promoting cytokines, TGF-β and G-CSF, as well as NET formation, have been frequently observed in TN breast cancer [69][70][71]. Due to the lack of information on neutrophil characterization in breast cancer subtypes in previous publications, we can try to explain the association between low neutrophils and poor prognosis in patients with luminal breast cancer assuming that the tumor microenvironment of luminal tumors may induce neutrophil polarization toward the pro-immunogenic N1 phenotype.…”
Section: Discussionmentioning
confidence: 79%
“…The evidence that increased levels of neutrophils (both peripheral and in primary tumors) in triple-negative and HER2-positive tumors are associated with tumor progression and dismal prognosis is indicative of a prevalent N2 phenotype in these tumors. Consistently, overexpression of N2-promoting cytokines, TGF-β and G-CSF, as well as NET formation, have been frequently observed in TN breast cancer [69][70][71]. Due to the lack of information on neutrophil characterization in breast cancer subtypes in previous publications, we can try to explain the association between low neutrophils and poor prognosis in patients with luminal breast cancer assuming that the tumor microenvironment of luminal tumors may induce neutrophil polarization toward the pro-immunogenic N1 phenotype.…”
Section: Discussionmentioning
confidence: 79%
“…G-CSF and GM-CSF are important growth factors commonly upregulated in cancer, and their primary functions are to regulate the release of mature neutrophils from the bone marrow into the blood and to extend the survival of neutrophils (38,39). In addition, cytokines, including interleukins (IL-17A, IL-6) (10,12,25,40), interferons (IFN-b) (9), TNF-a (25), and TGF-b (5,8,24,28), have been linked to neutrophil recruitment and extended neutrophil survival, as well as regulating neutrophil function. While a growing number of studies report the effect of individual mediators on neutrophil recruitment and function, it is likely that antagonistic, additive, or synergistic effects of different classes of mediators are crucial for neutrophil recruitment and function in the context of cancer.…”
Section: Diffusible Mediators In the Tumor Nichementioning
confidence: 99%
“…Neutrophil navigation to the tumor niche could therefore be orchestrated by the interplay of different mediators. We recently reported that CXCR2 ligands, potentially growth-related oncogene (GRO) members (CXCL1/2/3), and TGF-b1, which are abundantly secreted by triple-negative breast cancer cells, concertedly induce robust neutrophil migration (24). TGF-b ligands belong to the TGF-b subfamily, with three known mammalian isoforms: TGF-b1, TGF-b2 and TGF-b3, of which TGF-b1 is the most commonly expressed.…”
Section: Interplay Between Tgf-b and Chemokines To Maximize Neutrophil Recruitmentmentioning
confidence: 99%
“…Additionally, it causes the mobilization of these cells from the bone marrow [ 198 ]. These processes lead to the recruitment of TAN [ 199 , 200 ] and granulocytic, myeloid-derived suppressor cells (G-MDSC) [ 195 , 201 , 202 ] into the tumor niche. In doing so, this chemokine also increases the expansion of monocytic, myeloid-derived suppressor cells (Mo-MDSCs) in the bone marrow, which increases the number of these cells in the body, and thus in the tumor after the recruitment of these cells by other chemokines [ 203 ].…”
Section: Significance Of Cxcl1 In Tumorsmentioning
confidence: 99%